2018
DOI: 10.1111/sode.12284
|View full text |Cite
|
Sign up to set email alerts
|

Unsociability in Chinese adolescents: Cross‐informant agreement and relations with social and school adjustment

Abstract: We examined cross-informant agreement of unsociability and associations of unsociability with social and school adjustment. Participants were 229 (48% girls; M age 5 14.25, SD 5 .78 years) seventh-and eighth-graders in Liaoning, China. Unsociability and shyness were assessed with self-reports and peer nominations. Social and school adjustment data were obtained from multiple sources (self-, peer-, teacher-reports). Peer-reported unsociability was not significantly correlated with self-reported unsociability, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
(106 reference statements)
2
19
2
2
Order By: Relevance
“…We contributed novel information regarding self–peer agreement for avoidance; we found that self‐ and peer reports for avoidance were not associated significantly. Consistent with expectations and findings in samples from several cultures, self‐ and peer reports were associated significantly for shyness (Bayram Özdemir et al, ; Ding et al, ; Spangler & Gazelle, ; Zhang & Eggum‐Wilkens, ). We expected weaker cross‐informant agreement for unsociability, but self‐ and peer reports were not associated significantly.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…We contributed novel information regarding self–peer agreement for avoidance; we found that self‐ and peer reports for avoidance were not associated significantly. Consistent with expectations and findings in samples from several cultures, self‐ and peer reports were associated significantly for shyness (Bayram Özdemir et al, ; Ding et al, ; Spangler & Gazelle, ; Zhang & Eggum‐Wilkens, ). We expected weaker cross‐informant agreement for unsociability, but self‐ and peer reports were not associated significantly.…”
Section: Discussionsupporting
confidence: 79%
“…Peer‐reported unsociability and avoidance instead were significantly associated with self‐reported shyness. Peer‐reported unsociability similarly has demonstrated stronger associations with self‐reported shyness than self‐reported unsociability in other studies (Bayram Özdemir et al, ; Spangler & Gazelle, ; Zhang & Eggum‐Wilkens, ). The finding that the association between self‐reported shyness and peer‐reported unsociability exceeded the cross‐informant association for unsociability now has been replicated in samples of different ages, in different countries, and using different measures of withdrawal subtypes.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations